Child maltreatment and post-traumatic growth: Implications for the well-being of young adults. (September 2022) - Jankovic, Cassandra; Sharp, Jessica; Thielking, Monica
Abstract: Background: Little is known about the relationship between childhood maltreatment and well-being in young adults, including the role of post-traumatic growth (PTG) in promoting better outcomes for young adults who have a history of childhood maltreatment (HCM). Objective: To examine the relationship between child maltreatment and well-being among young adults, by considering the perpetrator and the extent of the maltreatment, as well as PTG among young adults with a HCM. Participants and setting: The sample comprised 537 young adults (aged 18–25; M  = 21.09 years, SD  = 2.36) from across Australia, with 182 young adults in the sample forming the cohort with a HCM. Method: Participants' current well-being, the extent of maltreatment by their mother, father and other adults experienced as a child (<18 years), and PTG was collected using an online survey. Tests of group differences and multiple regression were conducted to analyse the relationships between child maltreatment, PTG, and current well-being. Results: Maltreatment by one's mother or father predicted poorer current well-being, but not maltreatment by another adult. Young adults who identified as having a HCM had poorer well-being than those who did not. Within the cohort of those with a HCM, greater PTG predicted greater well-being, and also mitigated the negative relationship between child maltreatment by one's father and well-being. Conclusion: Findings indicate that both the extent of child maltreatment and the relationship to the perpetrator have implications for well-being among young adults. PTG appeared to play a protective role, highlighting the potential therapeutic benefit of fostering PTG to improve well-being among young adults with a HCM. Highlights: Both the extent of child maltreatment and the perpetrator have implications for well-being among young adults. Child maltreatment by one's mother or father predicted poorer current well-being, but not maltreatment by another adult. Greater PTG predicted greater well-being among young adults with a history of child maltreatment. Greater PTG mitigated the negative relationship between child maltreatment by one's father and current well-being.